1993
DOI: 10.1172/jci116558
|View full text |Cite
|
Sign up to set email alerts
|

Elevated sympathetic nerve activity in patients with accelerated essential hypertension.

Abstract: To determine if an abnormality exists in the sympathetic nervous system of patients with accelerated hypertension, we recorded muscle sympathetic nerve activity (MSNA) from the tibial nerve by microneurography in eight benign essential hypertensives and seven accelerated essential hypertensives. Basal MSNA, plasma renin activity, and plasma angiotensin II levels were significantly higher in accelerated hypertensives than in benign hypertensives (P < 0.05). To clarify the relationship between the renin-angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 19 publications
1
22
0
4
Order By: Relevance
“…5 This may operate through the adoption of less healthy lifestyles and general neglect of health by the patients, or through the stimulation of the sympathetic nervous system. Elevated sympathetic nerve activity has been found in accelerated hypertension, 16 and may act by stimulating renin release, increasing vasomotor tone and vascular permeability, and promoting the proliferation of vascular cells. 17 However, the inability to implicate stress per se in the aetiopathogenesis of hypertension 12 and our use of a reporting of perceived stress rather than a structured questionnaire might reduce the strength of the association between stress and MHT found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…5 This may operate through the adoption of less healthy lifestyles and general neglect of health by the patients, or through the stimulation of the sympathetic nervous system. Elevated sympathetic nerve activity has been found in accelerated hypertension, 16 and may act by stimulating renin release, increasing vasomotor tone and vascular permeability, and promoting the proliferation of vascular cells. 17 However, the inability to implicate stress per se in the aetiopathogenesis of hypertension 12 and our use of a reporting of perceived stress rather than a structured questionnaire might reduce the strength of the association between stress and MHT found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hypertension, MSNA has been reported to be higher than [5][6][7] or similar to 8 -10 measurements in normotensive control subjects. Studies in normal subjects have reported that MSNA is linked to heart rate (HR) 11 but is unrelated to blood pressure.…”
mentioning
confidence: 57%
“…Hypertension blunts baroreflex sensitivity (BRS) and vascular compliance [29,30] , and therefore may lead to the occurrence of OH. In contrast, OHT may be related to the [31,32] . Excessive venous pooling in the lower extremities upon standing can lead to a decrease in cardiac output, which may result in vigorous activation of the sympathetic nervous system and excessive arteriolar vasoconstriction in hypertensives with sympathetic hyperactivity, thus causing OHT.…”
Section: Discussionmentioning
confidence: 93%